The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1016/j.msea.2015.12.092
|View full text |Cite|
|
Sign up to set email alerts
|

Combined microtomography, thermal desorption spectroscopy, X-ray diffraction study of hydrogen trapping behavior in 7XXX aluminum alloys

Abstract: In the present study, combined thermal desorption spectroscopy (TDS), microtomography and X-ray diffraction study has been carried out to identify the hydrogen trap sites in 7XXX aluminum alloys. Through constant heating rate TDS experiments, three distinct trap states have been identified. It is revealed that micropores are the predominant hydrogen trap site in alloys with medium hydrogen content, whereas grain boundaries is the major hydrogen trap site in alloys with low and high hydrogen content. We have cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 56 publications
(9 citation statements)
references
References 54 publications
(64 reference statements)
0
8
0
Order By: Relevance
“…The dislocation densities were evaluated using the Williamson-Hall method 35 . The detailed procedure to estimate dislocation density was explained in our previous study 36 and the value was estimated to be 4.07 × 10 14 m −2 31 . The volume and surface area of all the pores present in the gauge region of the prepared alloys were analysed using the marching cubes algorithm 37 , where the three-dimensional morphology of pores can be measured by synchrotron X-ray tomography.…”
Section: Hydrogen Partitioningmentioning
confidence: 99%
“…The dislocation densities were evaluated using the Williamson-Hall method 35 . The detailed procedure to estimate dislocation density was explained in our previous study 36 and the value was estimated to be 4.07 × 10 14 m −2 31 . The volume and surface area of all the pores present in the gauge region of the prepared alloys were analysed using the marching cubes algorithm 37 , where the three-dimensional morphology of pores can be measured by synchrotron X-ray tomography.…”
Section: Hydrogen Partitioningmentioning
confidence: 99%
“…10) Reducing the hydrogen concentration in a material also leads to HE suppression. 11,12) However, to prepare a material with low hydrogen concentration, fabrication and thermal treatments must be performed under high vacuum conditions that are commercially not viable. 12) Recently, Tsuru et al revealed that the MgZn 2 precipitate interface spontaneously debonds as a result of hydrogen accumulation, and proposed this as a new mechanism for quasi-cleavage fracture in AlZnMg alloys.…”
Section: Introductionmentioning
confidence: 99%
“…11,12) However, to prepare a material with low hydrogen concentration, fabrication and thermal treatments must be performed under high vacuum conditions that are commercially not viable. 12) Recently, Tsuru et al revealed that the MgZn 2 precipitate interface spontaneously debonds as a result of hydrogen accumulation, and proposed this as a new mechanism for quasi-cleavage fracture in AlZnMg alloys. 13) It can be inferred that quasi-cleavage fracture is suppressed by reducing the hydrogen concentration at the MgZn 2 precipitate interface.…”
Section: Introductionmentioning
confidence: 99%
“…Al-Zn-Mg(-Cu) alloys are high-strength aluminum alloys that are widely used in aircraft and rolling stock, which require high strength-to-weight ratios. When the Zn or Mg content is increased to improve strength, susceptibility to stress corrosion cracking (SCC) increases, leading to delayed fracture [1][2][3] . Therefore, the SCC susceptibility of commercial alloys is suppressed both by adding trace elements such as Cr and Zr and by heat treatments such as overaging and retrogression-and-reaging treatments; the latter is a three-step heat treatment consisting of pre-aging, retrogression, and re-aging [4] .…”
Section: Introductionmentioning
confidence: 99%
“…According to Eqs. (1) and (2), the hydrogen partitioned to each trap site increases as the trap-site density and binding energy increase. Unlike the binding energy, the trap site density readily varies because of the thermal history and deformation [2,13,14,20] .…”
Section: Introductionmentioning
confidence: 99%